DIGITAL TRANSFORMATION AND SUSTAINABLE DEVELOPMENT OF BEVERAGE FIRMS IN PORT HARCOURT (UNIZIK Journal of Marketing, 2025)
This study investigated the connection between digital transformation and sustainable development within the context of beverage firms in Port Harcourt, Nigeria. The objective is to determine the relationship between digital transformation and sustainable Development of Food and Beverage Firms in Port Harcourt. As global business environments evolve, the adoption of digital technologies has become essential for enhancing operational efficiency, innovation capacity, and long-term sustainability. This paper applied a descriptive statistics and quantitative approach, while the population comprised of 23 registered food and beverages firms in Port Harcourt, Rivers State, Nigeria. The combination of random sampling and purposive sampling technique were adopted. The food and beverages firms were selected using purposive sampling technique, while random sampling was used to select 12 food and beverages firms in Port Harcourt. The research explores how digital tools, such as automation, data analytics, and integrated management systems are being leveraged to address the economic, environmental, and social dimensions of sustainability in the beverage industry. This paper adopted quantitative correlation approach of analysis. The findings reveal that digital transformation significantly contributes to improved resource utilization, reduced production waste, streamlined supply chain management, and enhanced customer engagement. Furthermore, digitalization supports corporate social responsibility initiatives and workforce development, thereby reinforcing the social aspect of sustainability. The paper concludes that while digital transformation is not a panacea, its strategic implementation can serve as catalyst for sustainable development in Nigeria’s beverage sector. It therefore recommends targeted investments in digital infrastructure, capacity building and policy frameworks that incentivize digital innovation aligned with sustainability goals.
Keywords: Digital transformation, sustainable development, Digital technology, resource efficiency, innovation.